Psychoneurobics: A Therapy for De-Addiction from Drugs and De-Stressing Prisoners: Harnessing the power of psychoneurobics for addiction recovery and prisoner well-being (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A study was led on Prisoners of District Jail of Himachal Pradesh. Psychoneurobic practice on de-fixation and de-worrying among Prisoners. Psychoneurobics is an Energy Therapy. In psychoneurobic, we breathe in the infinite vitality through the intensity of brain and after that exchange it to our body, psycho-neuro-respiro-immuno framework. Psycho Neurobics is the activities of moving otherworldly Energy in neuro cells by associating (mind) to the Supreme Source of Spiritual Energy (GOD). It is the best methodology to control your psyche with the end goal to use mind control for innovative work, to recuperate your body and to keep body and mind solid. It is a trident approach with neuro-strong respiratory activity sound vibrations and representation of various shades of imperceptible mending beams originating from the Almighty GOD make Psycho Neurobics profoundly viable to guarantee a fix from different addictions, push and related diseases. The exploratory approach is utilized on the detainees who were dependent of medications to discharge their worry for a time of three months (23.05.2017 to 01.0.2017). The detainees were estimated before the psychoneurobic practice session (Pre-test). They were prepared for psychoneurobics and taught to work on edifying and merry neurobics. According to the report shared by Dy. Superintendent, District and Open Air Jail of Himachal Pradesh. Every one of these detainees were snared to drugs and their de-fixation was a test before the prison organization. Be that as it may, the act of psychoneurobics has rolled out huge commitment in getting improvement the state of mind of detainees. With the normal routine with regards to this activity colossal effect on these detainees were watched. Presently they contemplate their lives and they have neither propensity for medications nor require any assistance to manage enslavement.